(untitled) (Significação: Journal of Audiovisual Culture, 2003)
Houve uma Vez Dois Verdes (2002), Jorge Furtado's first feature film, updates the recurrent thematic association seaside/adolescence or youth in the urban cinema ofRio Grande do Sul. In films like Deu Pra Ti Anos 70 (Nelson Nadotti and Giba Assis Brasil, 1981) and Inverno (Carlos Gerbase, 1982), such association builds up, through the representation of seaside as a transitional space typical of adolescence, allied to the adherence of gaucho urban cinema to a project of autonomization of the gaucho urban identity, meanings of "escape from the pampa" or from the gaucho rural identity then dominant. Furtado's film reworks the thematic association narrating the experience of a new adolescent generation. To do that, it adopts, while simultaneously ideologically weakening them, the subgeneric conventions of the beach party movie and the nostalgic teen film